Experimental Study of the Reduction of the Dose to the Radiographic Operator Using an Additional Rectangular Collimator and Detector Holder During Handheld Exposure with a Portable Intraoral X-Ray Device - Yusei Otaka; Yasuo Harata; Maki Izawa; Noriyoshi Shiba; Nobutoshi Takahashi; Shinji Kito (Journal of Indian Academy of Oral Medicine and Radiology)
Background: Use of a rectangular collimator and a detector holder reduces the patient’s dose in intraoral radiography; however, their quantitative effects on reducing the operator’s dose are unknown. Objectives: This study aimed to evaluate the reduction in the operator’s dose when using a rectangular collimator and a detector holder during handheld exposure with a portable intraoral X-ray device. Materials and Methods: Dose was measured using a cylindrical polymethylmethacrylate phantom and two semiconductor dosimeters. Stray radiation from the phantom and the X-ray device was measured at 15-degree intervals in horizontal and vertical circles with radii of 50 cm and 100 cm from the center of the phantom. Doses were compared with and without the additional rectangular collimator and the detector holder. Results: Use of the additional rectangular collimator and the detector holder reduced the operator’s dose to one-eighth and one-fifth, respectively, of the dose when these items were not used. Conclusion: Using an additional rectangular collimator and a detector holder appears effective for reducing the dose to the radiographic operator during handheld exposure with a portable intraoral X-ray device and could be applied to situations such as dental home health care and person identification in forensic dentistry.